2017
DOI: 10.1111/jce.13229
|View full text |Cite
|
Sign up to set email alerts
|

Study of the wearable cardioverter defibrillator in advanced heart‐failure patients (SWIFT)

Abstract: Introduction The wearable cardioverter defibrillator (WCD) may allow stabilization until reassessment for an implantable cardioverter defibrillator (ICD) among high‐risk heart failure (HF) patients. However, there are limited data on the WCD benefit in the acute decompensated HF setting. Methods and results The Study of the Wearable Cardioverter Defibrillator in Advanced Heart Failure Patients (SWIFT) was a prospective clinical trial carried out at two medical centers. Patients hospitalized with advanced HF sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…As we know from other studies on WCD therapy [ 3 5 , 17 , 18 ], the overall incidence rate of shock therapy is low; therefore the number needed to treat to save one patient from SCD by WCD therapy will be quite high and it is an expensive therapy (in Germany the monthly cost amounts to roughly 2650 euros). In addition, WCD therapy remarkably diminishes QoL in our collective.…”
Section: Discussionmentioning
confidence: 99%
“…As we know from other studies on WCD therapy [ 3 5 , 17 , 18 ], the overall incidence rate of shock therapy is low; therefore the number needed to treat to save one patient from SCD by WCD therapy will be quite high and it is an expensive therapy (in Germany the monthly cost amounts to roughly 2650 euros). In addition, WCD therapy remarkably diminishes QoL in our collective.…”
Section: Discussionmentioning
confidence: 99%
“…After addition of two citations identified by hand search, forty-six primary studies, two systematic reviews, and one HTA were included for final analysis (see Figure 1). The forty-six primary studies included one RCT 7, one nrCT (11), sixteen non-comparative prospective trials (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), and twenty-eight non-comparative retrospective trials (4;28-54). The RCT showed a low and the nrCT a high risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…No patient in the study received inappropriate therapy delivery. At the end of the study, 28% of patients went on to permanent device implantation, and the cumulative mortality rate at 3 years in this population was 21% for patients with nonischemic cardiomyopathy compared to 21% for those with ischemic cardiomyopathy [19].…”
Section: Nyha Class IV Heart Failurementioning
confidence: 96%
“…No inappropriate therapies were delivered, and no patients died in the course of the study. When the study concluded, 28% were implanted with an ICD [19].…”
Section: Clinical Trials and Other Evidencementioning
confidence: 99%